1997
DOI: 10.1016/s0022-5223(97)70026-6
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged hemodynamic stability during arteriovenous carbon dioxide removal for severe respiratory failure

Abstract: Arteriovenous carbon dioxide removal as a simplified means of extracorporeal gas exchange support is relatively safe without adverse hemodynamic effects or complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
(4 reference statements)
0
18
0
1
Order By: Relevance
“…Our data confirmed, despite a 20% to 26% cardiac shunt, that AVCO 2 R can be used for total CO 2 removal for up to 7 days, without hemodynamic compromise or instability, in an adult sheep model of severe respiratory failure. 60 A 10F arterial and 12F venous percutaneous cannula will allow an arteriovenous shunt flow Ͼ500 ml/min and provides some lung rest with permissive hypercapnia. 57 Brunston et al 59 reported that a normal pCO 2 could be maintained with minimal ventilator support at blood flows of 500 ml/min or more.…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirmed, despite a 20% to 26% cardiac shunt, that AVCO 2 R can be used for total CO 2 removal for up to 7 days, without hemodynamic compromise or instability, in an adult sheep model of severe respiratory failure. 60 A 10F arterial and 12F venous percutaneous cannula will allow an arteriovenous shunt flow Ͼ500 ml/min and provides some lung rest with permissive hypercapnia. 57 Brunston et al 59 reported that a normal pCO 2 could be maintained with minimal ventilator support at blood flows of 500 ml/min or more.…”
Section: Discussionmentioning
confidence: 99%
“…There was sufficient hemodynamic stability to ensure a pressure gradient between the arterial and venous vasculature. (2) In addition to improved gas exchange and CO 2 removal, the radiological progression was satisfactory. Regarding gas exchange, the major benefit of iLA is CO 2 removal, with little effect on oxygenation.…”
Section: Letter To the Editormentioning
confidence: 86%
“…Hypercapnia can be treated with extracorporeal membrane oxygenation (ECMO), which requires a complex apparatus and is associated with side effects, the use of ECMO being therefore limited to referral centers. In contrast with ECMO, interventional lung assist (iLA), which promotes gas exchange for CO 2 removal without the use of a pump, is carried out via an artificial shunt, which is placed by means of arterial and venous dissection. The use of iLA is indicated for the control of respiratory acidosis and hypoxemia caused by high CO 2 levels (> 80 mmHg) during protective ventilation.…”
mentioning
confidence: 99%
See 2 more Smart Citations